Shake Shack IPO - Bourg-Meyer, Vero; Elias, Jaan; Thomas, Jake; Rouwenhorst, Geert (London : Yale School of Management, 2016)
When famed fine-dining restaurateur Danny Meyer opened a hot dog cart in New York City's Madison Square Park in 2001, the venture drew legions of customers curious to experience Meyer's take on all-American street food. The curious became the committed and Meyer's little experiment acquired a permanent structure in the park - the Shake Shack. The Shack regularly drew long lines, leading Meyer to build a company around the concept. In a few years, Shake Shack expanded to a chain of burger restaurants in the United States and licensed outlets internationally.Meyer sought to differentiate Shake Shack from the long tradition of burger joints and chains that dotted the American landscape. First, Shake Shack was committed to high quality ingredients and efficient operations in each of its eateries. Secondly, the company selected high traffic locations and designed each outlet to fit into its chosen locale. Finally, Meyer wanted Shake Shack employees to create culture of hospitality that welcomed each customer as if Shake Shack was a fine-dining establishment, rather than a burger joint.
Originally published in Bourg-Meyer, V., Elias, J., Thomas, J. & Rouwenhorst, G. (2016). Shake Shack IPO. 16-021. New Haven, CT: Yale School of Management, Yale University. Retrieved from: https://vol11.cases.som.yale.edu/shake-shack-ipo.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Meyer, Danny; Shake Shack (Restaurant chain) -- Management